The Influence of Information Quality and Website Quality on Repurchase Intention with Website-Based Customer Satisfaction as a Mediating Variable in Shopee and Tokopedia Applications - Nanda Meisya Putri; Moechammad Nasir; Rini Kuswati (LP2M IAIN Palopo, 2025)
The purpose of this study is to analyze the effect of Information Quality and Website Quality on Repurchase Intention with Customer Satisfaction as a mediating variable on the Shopee and Tokopedia applications. This research is an explanatory study with a quantitative approach. The population of this study is the community in the Madiun region (Madiun, Magetan, and Ponorogo regencies) who use the Shopee and Tokopedia applications. The sampling technique in this study uses a non-probability sampling method based on a purposive sampling approach. The number of samples used in this study was 300 respondents. The data used in this study was primary data. The data analysis technique in this study used Partial Least Square (PLS) with the help of SMARTPLS software. The results showed that customer satisfaction had a positive and significant effect on repurchase intention among Shopee and Tokopedia users. Information Quality and Website Quality also have a positive and significant effect on Customer Satisfaction on both platforms. In addition, Information Quality has a positive and significant effect on Repurchase Intention, while Website Quality is only significant on Tokopedia and not significant on Shopee. Customer Satisfaction is proven to mediate the effect of Information Quality and Website Quality on Repurchase Intention on both platforms.